Linke between The Activity of Daily Living and the Sense of Control among Patients with Chronic Liver Disease - Ghannam Abdel-Hussein Al-Nassar, Hawra'a; Salah Razzaq, Muntadher; Salah Razzaq, Maha (International Journal of Psychosocial Rehabilitation, 2020)
Background: Chronic liver disease (CLD) is a growing global health concern, contributing to increased mortality and morbidity rates worldwide. This complex condition predominantly affects individuals in their midlife and youth. In recent decades, the number of people affected by CLD has increased to around 550 million due to viral infections alone. The figure rises even higher when including other causes such as fatty liver disease, alcohol consumption, immune disorders, metabolic issues, and cholestasis.Methodology: A descriptive correlational design was utilized in this study to assess the activities of daily living (ADL) of CLD patients and their sense of control. The study period extended from February to May 2019. Data were gathered using the Arabic version of a structured questionnaire, administered through interviews with patients at the Gastroenterology and Hematology Center in Al-Sadder Medical City. Data collection took place between March 17, 2019, and April 5, 2019.Results: The findings indicate that the overall assessment of CLD patients' ADL was categorized as *independent*, and their overall sense of control was classified as *moderate*. A significant direct correlation was identified between the ADL of patients and their sense of control. This means that as patients' ADL improved, their sense of control also increased, and vice versa.Conclusions: The study concludes that CLD patients generally demonstrate a good level of ADL, but their sense of control is less than ideal. Furthermore, there is a direct and positive impact of patients' ADL on their sense of control.Recommendations: The study recommends further research to identify and develop effective strategies to enhance the ADL and sense of control in CLD patients. Additionally, educational booklets containing information and instructions on ADL and sense of control for CLD patients should be developed and distributed.